EXPLORING THE IMPACT OF PAYLATER PAYMENTS ON CONSUMER BEHAVIOR AND PUBLIC FINANCIAL MANAGEMENT: A SYSTEMATIC LITERATURE REVIEW - Anggorowati, Luki Sri (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2025)
The development of financial technology has driven the emergence of various innovations in payment systems, one of which is the paylater service or "buy now, pay later." This service has been widely adopted by marketplace platforms to enhance consumer convenience. This literature review aims to analyze the impact of paylater services on the increase in consumerist behavior among marketplace users. The method used in this study is a Systematic Literature Review (SLR) of journal papers published from 2022 to 2025. Based on the review of various studies, it was found that easy access, quick approval processes, and minimal psychological barriers in making purchases contribute to increased frequency and transaction value among consumers. This review concludes that paylater services tend to encourage consumerist behavior, particularly among the younger generation who actively use digital platforms. The study recommends the need for digital financial literacy so that users can make wiser use of these services.